Adsorption Technology in Water Treatment Fundamentals, Processes, and Modeling - Worch, Eckhard (De Gruyter, 2021)
This book treats the theoretical fundamentals of adsorption technology for water treatment from a practical perspective. It presents all the basics needed for experimental adsorption studies as well as for process modeling and adsorber design. According to the increasing importance of micropollutants in the water cycle, particular attention is paid to their competitive adsorption in the presence of background organic matter. The current edition considers recent developments in adsorption theory and practice.